BIMBINGAN SPIRITUAL; SOLUSI PENGOPTIMALAN KARAKTER ANAK USIA DINI DI MASA DEPAN - Panji Achmad Faqih Zamany, Raden; Faizal Umam As-Shobri, Ach.; Rosyidah, Rosyidah; Suaidah, Suaidah (IDEALITA: Jurnal Pendidikan dan Sosial Keagamaan, 2022)
Spiritual guidance not only has a very big role in shaping the character of children, but it will become a life guide as a milestone in realizing a good and useful personality for others. This study aims to describe the optimization of the development of early childhood spiritual intelligence in learning. Islam in school. This type of research is field research or field research. This research is presented in descriptive form. While the method used is a qualitative method. Data collection techniques used are observation, interviews, and documentation. While the data analysis technique uses the Miles and Huberman Model, which consists of: Data Reduction, Data Presentation, and Verification. The results of this study indicate that optimizing the development of spiritual intelligence can be done by instilling the habit of good things in accordance with the Qur'an and hadith in children from an early age. Learning applied in schools can help in the development of children's spiritual intelligence because it is designed creatively and fun by teachers who are competent in their fields such as using group models, contextual approaches, and using story methods, memorization, singing, and song movement exercises.